The influences of institution attended and field of study on graduates’ starting salaries - Birch, E.; Li, I.; Miller, Paul (Blackwell Publishing Asia, 2009)
This paper examines the determinants of Australian university graduates' starting salaries, with an emphasis on the institution attended and field of study. It is shown that there is little difference between the starting salaries of students who attended Group of Eight universities and those who attended other universities. There are modest differences in starting salaries across fields of study. However, these differences are considerably less than those associated with the type of employment obtained. These results suggest it is what you do in the labour market, rather than where or what you have studied, that is the main determinant of labour market outcomes.